A Model of Job Opportunity Creation through Basic Skill Empowerment for Housewives - Muslim, Azis (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2015)
Lower economic level of family often encourages the woman contributes to earning living, thus woman plays a double role. Actually, playing a double role as housewife and as living earner is not a serious problem for women. The problem becomes serious when her role is added with children caretaking. The children caretaking job cannot be overridden. For that reason, many women are willing to abandon their role as living earner only for taking care of children. This research aimed to explore a model of creating job opportunity the administrators of PKK (Family Welfare Empowerment) make in their attempt of helping housewives find appropriate job in their house environment, so that housewives can maximize their role and take care of their children all at once. Considering the result of research, it can be Â found that the job opportunity creation model started with identifying the root of problem the housewives encounter, after which is followed with identifying skill and potential to be utilized, and then formulating the solution. This model, despite simplicity, can be fruitful when it is conducted persistently, thoroughly and smartly. The success is indicated with the increased income of the members.Â